Implementasi Kebijakan Jaminan Produk Pangan Halal di Kota Palangka Raya Provinsi Kalimantan Tengah - Hamberi Hamberi; Bayu Dwi Saputra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to determine how the Implementation of Law number 33 of 2014 concerning Halal Product Assurance in the City of Palangka Raya, Central Kalimantan province. The type of research used is qualitative research methods with descriptive analysis techniques. The informants taken in this study were conducted using purposive sampling and snowball sampling techniques. Based on the results of research on the implementation of Law no. 33 of 2014 concerning guarantee of halal products in the city of Palangka Raya, Central Kalimantan province, it can be concluded that the implementation has been carried out but has not run optimally and has not provided meaningful changes to the community. The advice that researchers can give to the organizers of the guarantee policy for halal products in the city of Palangka Raya should be to collaborate more with agencies and communities so that the halal product certification policy can run properly